Molecular targets and anti-cancer potential of escin - Cheong, D.; Arfuso, Frank; Sethi, G.; Wang, L.; Hui, K.; Kumar, Alan Prem; Tran, T. (Elsevier, 2018)
Escin is a mixture of triterpenoid saponins extracted from the horse chestnut tree, Aesculus hippocastanum. Its potent anti-inflammatory and anti-odematous properties makes it a choice of therapy against chronic venous insufficiency and odema. More recently, escin is being actively investigated for its potential activity against diverse cancers. It exhibits anti-cancer effects in many cancer cell models including lung adenocarcinoma, hepatocellular carcinoma and leukemia. Escin also attenuates tumor growth and metastases in various in vivo models. Importantly, escin augments the effects of existing chemotherapeutic drugs, thereby supporting the role of escin as an adjunct or alternative anti-cancer therapy. The beneficial effects of escin can be attributed to its inhibition of proliferation and induction of cell cycle arrest. By regulating transcription factors/growth factors mediated oncogenic pathways, escin also potentially mitigates chronic inflammatory processes that are linked to cancer survival and resistance. This review provides a comprehensive overview of the current knowledge of escin and its potential as an anti-cancer therapy through its anti-proliferative, pro-apoptotic, and anti-inflammatory effects.